High Resolution Algorithms Applied to Velocity and Length-of-Travel Measurements in Radar Sensors - Stelzer, Andreas; Pichler, Markus; Weigel, Robert (Asia-Pacific Microwave Conference (APMC), 2002)
This work presents results of the application of high-resolution frequency estimation algorithms to Doppler-radar signals for velocity and length-of-travel calculation. The measurement of velocity or distance of remote targets is a very common task in industrial applications, and especially under rough environmental conditions a radar sensor is the solution of choice. The fast Fourier transformation (FFT) – widely used for signal evaluation – exhibits inherent resolution limitations. Therefore, many high-resolution frequency estimation algorithms have been developed in the last decades, and their application to measured radar data with multiple targets is shown.
elib2cris::1512001600,stelzer2002a
Keywords: Doppler-radar; frequency estimation; velocity measurements; microwave sensors